Diagnóstico de manifestações patológicas em alvenaria estrutural: estudo de caso na Cidade de Palmas/TO - Macedo, Lucas de Oliveira (Universidade Federal do Tocantins, 2020)
The structural masonry is gaining the spotlight in these past decades in Brazil, being each time more and more employed, especially in social interest enterprises. This work was developed based on these principals. The study highlighted three residential sets, administrated by the municipal town hall and financed by PAC. These enterprises are located in the city of Palmas in the Tocantins state. The objectives of the research were: take into account the pathological manifestations, determine causes, to offer solutions and elaborate a budget connected to the conclusions. In order to obtain success in the research visits to the sites were made, project analyses and a bibliography study. In addition, it was elaborated an analysis of the pathological manifestations by direct observation. Therefore, it became possible to identify the propelling causes for the pathologies detected. Also, there were discussions about the precepts of the constructive process, the phases of the project and its execution that worked as a preventive measure to these problems. Besides this, discourses were held involving the GUT method and the viability technique and the enterprises financially stability into question.